Analisis Puisi “pada suatu Hari Nanti” Karya Sapardi Djoko Damono: Kajian terhadap Jenis Makna dalam Ilmu Semantik - Puspa Ningrum, Aisyah Tinus; Dalimunthe, Anisah Azzahra; Yuhdi, Achmad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The use of many figurative words makes it difficult for readers to understand the meaning contained in the beautiful stanzas of poetry. The purpose of the research is to analyze semantically with the object of study of a poem entitled "Pada Satu Hari Nanti" written by Sapardi Djoko Damono. This research is studied through semantic analysis to examine the meaning that focuses on analyzing lexical meaning, grammatical meaning, referential meaning, and connotative / figurative meaning. In accordance with the above objectives, the type of research is descriptive qualitative research. Data collection is done using documentation techniques, library techniques, and note-taking techniques. The results of the analysis show that in each stanza of the poem there is a complexity of lexical, referential, grammatical, and connotative/figurative meanings that provide depth and richness of meaning in poetry as well as broader knowledge of the use of language in literary works and how meaning can be interpreted through semantic analysis. The use of many figurative words makes it difficult for readers to understand the meaning contained in the beautiful stanzas of poetry. The purpose of the research is to analyze semantically with the object of study of a poem entitled "Pada Satu Hari Nanti" written by Sapardi Djoko Damono. This research is studied through semantic analysis to examine the meaning that focuses on analyzing lexical meaning, grammatical meaning, referential meaning, and connotative / figurative meaning. In accordance with the above objectives, the type of research is descriptive qualitative research. Data collection is done using documentation techniques, library techniques, and note-taking techniques. The results of the analysis show that in each stanza of the poem there is a complexity of lexical, referential, grammatical, and connotative/figurative meanings that provide depth and richness of meaning in poetry as well as broader knowledge of the use of language in literary works and how meaning can be interpreted through semantic analysis.